PENGARUH ANHIDRIDA ASAM MALEAT TERHADAP SIFAT-SIFAT SABUN GONDORUKEM - Toga Silitonga (Jurnal Penelitian Hasil Hutan, 1988)
Levopimaric  acid,  with its two double  bonds conjugated  in the same ring, can react with α-, β-  unsaturated  carbonyl  compounds in a Diels - Alder  reaction.  This reaction  is the basis for preparation  of fortified   rosin soap by addition  of. maleic  unhydride.   The  research purpose  is to study  the influence  of maleic unhydride  addition  on moisture  content,  total rosin, combined  rosin,  free rosin,  and unsaponifiable  matter  of rosin soap properties.Results   indicate  that  the  inclusion  of  maleic  unhydride   during  the  soap  making  process  has  a highly  significant effect on  the  overall  rosin  soap properties. Furthermore. The LSD  test of the difference   between  unfortified and fortified rosin soap properties  appeared  to  be highly  significant  in favor  of  the fortified one.  Therefore, it is advisable to fortified rosin soap for  better  and efficient result in the rosin size manufactures.